Kaci Taing: capstone - Taing, Kaci, artist (Colorado State University. Libraries, 2026)
The artist's statement: I feel the most authentic as an artist when drawing the human experience. My work consists of personal experiences expressed through realistic portraiture by the use of addition and subtraction of line and form. My inspiration comes from my day to day life. I am attracted to depicting human interaction, fragments of life, interpersonal relationships, social dynamics, and life transitions. Capturing moments through art itself feels important to me and strengthens my passion for creating. My work is heavily processed based. Working in layers by the act of taking away and reapplying materials, allows my work to transform into art that is not predetermined. I find that the beauty of my work is concentrated in the 'pretty and the grit'; having a balanced piece, whether that is through color with charcoal or smooth texture with rough edges. I am fond of the stark contrast of an abstract background with an integrated realistic portrait. My artwork is expressed with multimedia materials: conte, chalk, charcoal, colored pencils, ink, and graphite.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing